Role of Sonoelastography in Differentiating Benign and Malignant Breast Lesions: A Prospective Study Comparing Elasticity Contrast Index and Tsukuba Score (Nepalese Journal of Radiology, 2024)
Introduction: Breast cancer is the most common cancer occurring in women globally which is potentially curable if detected early. Ultrasound elastography is a dynamic technique that estimates tissue stiffness to differentiate between benign and malignant masses. Our study aimed to determine and compare the diagnostic accuracy of B mode Sonography, Elasticity contrast index, and Tsukuba score in differentiating malignant and benign breast masses.Methods: This was a prospective cross-sectional study done including 110 lesions in 102 patients in the age group of 15-73 years. The solid breast lesions seen on sonography were categorized according to the American College of Radiology Breast Imaging Reporting and Data System (ACR BI-RADS) and further evaluated with elastography using both Elasticity Contrast Index (ECI) and Tsukuba score with pathological diagnosis taken as the gold standard. The cut-off value of ECI was obtained. The diagnostic accuracy of B-mode sonography, ECI, and Tsukuba score was compared.Results: We found that B-mode sonography had a sensitivity of 85.7%, specificity of 100%, and accuracy of 96.9 %. The accuracy of Tsukuba scores for differentiating benign and malignant lesions was 81.2%. The cut-off value of ECI obtained was 2.8 and the accuracy was 81.8%. A statistically significant correlation (p < 0.05) existed between sonographic diagnosis, ECI, and Tsukuba score.Conclusions: B mode sonography had the highest diagnostic accuracy while ECI and Tsukuba scores were comparable. ECI can be used for breast masses using a cut-off of 2.8 to differentiate benign from malignant.